2000
DOI: 10.1103/physrevlett.85.3057
|View full text |Cite
|
Sign up to set email alerts
|

Driven DNA Transport into an Asymmetric Nanometer-Scale Pore

Abstract: To understand the mechanism by which individual DNA molecules enter nanometer-scale pores, we studied the concentration and voltage dependence of polynucleotide-induced ionic-current blockades of a single alpha-hemolysin ion channel. We find that the blockade frequency is proportional to the polymer concentration, that it increases exponentially with the applied potential, and that DNA enters the pore more readily through the entrance that has the larger vestibule. We also measure the minimum value of the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
554
6
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 475 publications
(599 citation statements)
references
References 22 publications
38
554
6
1
Order By: Relevance
“…We should note, however, in the problem of biopolymer transport through a membrane pore, the role of specific interactions may become essentially important [9,10,13]. We neglect all the complications associated with such a factor and focused on universal aspects as a consequence of a polymeric nature, in this sense, the present analysis may be regarded as an "ideal" version in view of the relation with the problem of polymer translocation.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…We should note, however, in the problem of biopolymer transport through a membrane pore, the role of specific interactions may become essentially important [9,10,13]. We neglect all the complications associated with such a factor and focused on universal aspects as a consequence of a polymeric nature, in this sense, the present analysis may be regarded as an "ideal" version in view of the relation with the problem of polymer translocation.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Our target here is the dynamical process, in which a polymer is sucked into a localized hole. This is different from the pulling the chain's one end [8], but similar in the way how the chain responds to the local force, and, in fact, relevant to the dynamics of polymer translocation through hole [9,10] and the adsorption process to a small particle. (In this case, the force f is related to the chemical potential change ∆µ due to the absorption via f = ∆µ/b.)…”
Section: Introductionmentioning
confidence: 99%
“…Experimental articles published since that review have furthered our knowledge about this process. For instance, Kasianowicz' group [6] has determined that the rate of entry of ssDNA into an a-hemolysin channel increases linearly with DNA concentration and exponentially with the voltage difference applied along the channel. They also found that the rate of entry is higher when the DNA enters the channel through the protein's larger vestibule rather than through the other end.…”
Section: Nanopore Technologiesmentioning
confidence: 99%
“…This allowed determination of the minimum voltage required to keep a DNA -avidin complex trapped in an a-haemolysin nanopore to be around 70 mV [33]. A very similar approach can be used to immobilize a DNA strand and thus identify which of the four bases of DNA is located in the constriction [34,35].…”
Section: Modification Of the Translocating Moleculementioning
confidence: 99%
“…Nevertheless, this can be very useful for very specific questions about the molecular structure. One of the first experiments by Henrickson et al [33] demonstrated that DNA can be stalled in a protein nanopore in 2000.…”
Section: Modification Of the Translocating Moleculementioning
confidence: 99%